Comportamento da função de proteção ANSI 21 frente a mensagens sampled values corrompidas - Veloso, Juliana Freire (2024)
Currently, most IED manufacturers block the protection function during SV packet transmission. The protection function is inactive for the period that packets are corrupted. These blockages can interfere with the accuracy and reliability of the system's operation. In this sense, research on the behavior of protection functions in the face of possible SV package formation problems is important. Modern substations are implementing process bus communication networks based on IEC 61850-9-2 switched Ethernet to perform their protection functions. Packet loss is a relatively common phenomenon and plays a crucial role in implementing power system real-time protection applications based on time-critical communication networks. This work aims to demonstrate the behavior of distance protection in transmission lines in the face of packet corruption scenarios via SV communication. Tests were carried out on a virtual power system lHYPERSIM, to protect a transmission line. In real-time digital simulation of the implemented circuit, its behavior was analyzed during various fault scenarios. To test the circuit under single-phase electrical faults in various locations, 3 operational test scenarios were created. It was evident that the corruption of SVs packages significantly interferes with the IED's operating time, whether real or virtual. In the worst case scenario, the loss of SV packets, in the two parameterized operating zones, caused the TRIP to increase in time by up to 100%, seriously compromising the accuracy and reliability of the system's operation.